2021
DOI: 10.21203/rs.3.rs-229895/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ferulic Acid Inhibits Topoisomerase I of Mycobacterium Tuberculosis

Abstract: IntroductionVarious drugs are first line anti-TB drugs for more than thirty years. Since ferulic acid have shown promising inhibition growth of M. tuberculosis and M. smegmatis cell.ObjectiveIn this study, we have explored the inhibitory effect of ferulic acid against Mycobacterium tuberculosis topoisomerase I. We further investigated the mechanism of ferulic acid by various experiments.MethodsDNA relaxation assays was done for supercoiled pUC18 DNA, oligonucleotide cleavage assay was performed for 5ʹ-end-labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
2
0
0
Order By: Relevance
“…It is worth noting that ferulic acid bound as a competitive inhibitor ( Figure 1 D). This was observed in the present study as well as the study by Lu et al [ 27 ], who reported that ferulic acid can act as a competitive inhibitor of TOP at a concentration of 10–30 µM. The cited study showed that ferulic acid can inhibit cell proliferation in Procaryote by directly binding the DNA-gyrase complex [ 27 ].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…It is worth noting that ferulic acid bound as a competitive inhibitor ( Figure 1 D). This was observed in the present study as well as the study by Lu et al [ 27 ], who reported that ferulic acid can act as a competitive inhibitor of TOP at a concentration of 10–30 µM. The cited study showed that ferulic acid can inhibit cell proliferation in Procaryote by directly binding the DNA-gyrase complex [ 27 ].…”
Section: Resultssupporting
confidence: 89%
“…This was observed in the present study as well as the study by Lu et al [27], who reported that ferulic acid can act as a competitive inhibitor of TOP at a concentration of 10-30 µM. The cited study showed that ferulic acid can inhibit cell proliferation in Procaryote by directly binding the DNA-gyrase complex [27]. Additionally, Bandele et al [28] reported that polyphenols are a diverse and complex group of compounds that interact with the enzyme in a noncovalent manner but can also react by covalent adduction.…”
Section: Characterization Of the Complexes Of Chas And Caffeine With ...supporting
confidence: 93%